Does Oral Propranolol Accelerate Augmentation of Labour in Synergy with Oxytocin in Nulliparous Women? A Randomized Controlled Trial in Abakaliki, Nigeria
Objective: Propranolol, a beta blocker has been documented in few studies to act in synergy with oxytocin to accelerate labour progress. The only available systematic review is inconclusive, hence, the need for this study. Methodology: This research is a clinical superiority open labeled randomized controlled trial that involved only nulliparous women who met the inclusion criteria and gave consent to the study. Participants were randomized from a pool of 82 participants divided into A and B. Group A received 20 mg of oral propranolol and oxytocin titration while group B received only oxytocin titration. Partograph was used to monitor their labour. SPSS software was used for analysis. Continuous variables were analyzed using students t-test while chi-square (χ2) test was used for categorical variables. A P-value of <0.05 was considered significant. Results: The total mean duration of labour was statistically significant (P<0.001). The mean duration of active phase of labour was also statistically significant (P = 0.001). However, there was no significant difference in the 2nd stage (P=0.491)